1991
DOI: 10.1271/bbb1961.55.109
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of .ALPHA.-galactosidase from Aspergillus niger 5-16.

Abstract: This paper describes the specificity of Aspergillus niger 5-16 alpha-galactosidase toward various oligosaccharides having terminal galactose or stub galactose or both on the oligosaccharide. The galactosidase rapidly hydrolyzed p-nitrophenyl-alpha-D-galactopyranoside, but hardly liberated galactose from melibiose, manninotriose, 6(3)-alpha-D-galactosylmannotriose, etc. On the other hand, the enzyme tore off the stub galactoses attached to the inner mannoses of the main-chain of galactomannooligosaccharides, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…It is known (Varbanetes et al, 2001) that most microbial α-galactosidases hydrolyze the synthetic substrate ρNPGal more efficiently than the natural α-galactosides. Moreover, α-galactosidase from Aspergillus niger was reported (Kaneko et al, 1991) to hydrolyze exclusively the synthetic substrate and failed to split off the terminal α-1,6-bound galactose in linear structures like the melibiose, raffinose and stachyose. Nevertheless, previous findings indicated that α-galactosidases from T. reesei (Zeilinger et al, 1993) and Bifidobacterium breve (Xiao et al, 2000) were able to hydrolyze raffinose.…”
Section: Resultsmentioning
confidence: 99%
“…It is known (Varbanetes et al, 2001) that most microbial α-galactosidases hydrolyze the synthetic substrate ρNPGal more efficiently than the natural α-galactosides. Moreover, α-galactosidase from Aspergillus niger was reported (Kaneko et al, 1991) to hydrolyze exclusively the synthetic substrate and failed to split off the terminal α-1,6-bound galactose in linear structures like the melibiose, raffinose and stachyose. Nevertheless, previous findings indicated that α-galactosidases from T. reesei (Zeilinger et al, 1993) and Bifidobacterium breve (Xiao et al, 2000) were able to hydrolyze raffinose.…”
Section: Resultsmentioning
confidence: 99%
“…Mortierella vinacea ␣-Gal I (11) and yeast ␣-Gals (32) are specific for Gal 3 Man 3, having an ␣-galactosyl residue (designated the terminal ␣-galactosyl residue) attached to the O-to-6 position of the nonreducing end mannose of ␤-1,4-mannotriose. On the other hand, Aspergillus niger 5-16 ␣-Gal (12) and Penicillium purpurogenum ␣-Gal (27) show a preference for Gal 3 Man 4 , having an ␣-galactosyl residue (designated as the side chain ␣-galactosyl residue) attached to the O-to-6 position of the third mannose from the reducing end of ␤-1,4-mannotetraose. The M. vinacea ␣-Gal II (28) acts on both substrates to almost equal extents.…”
mentioning
confidence: 99%
“…Genes encoding ␣-Gals have been cloned from various sources, including humans (3), plants (20,33), yeasts (12), filamentous fungi (4,19,26,28), and bacteria (1,2,13,17,18). ␣-Gals from eukaryotes show a significant degree of similarity and are grouped into family 27.…”
mentioning
confidence: 99%
“…The capability of some a-galactosidases to release a-galactosyl side groups from galactomannans has also been studied. Enzymes that can act on intact polymeric galactomannan have been isolated from seeds of Cyumopsis tetragonoloba (guar; Bulpin et al, 1990), Phaseolus vulgaris (French bean; Dhar et al, 1994) and Vigna rudiuta (mung bean; Dey, 1984) and from filamentous fungi such as Aspergillus tamarii (Civas et al, 1984b), Aspergillus niger (Adya and Elbein, 1977;Kaneko et al, 1991) and Trichoderma reesei (Zeilinger et al, 1993). Some cx-galactosidases have no activity on galactomannan such as the one described for Mortierella vinacea (Kaneko et al, 1990).…”
mentioning
confidence: 99%